Evaluating the Potential of Container-Based Sanitation : SOIL in Cap-Haitien, Haiti - World Bank (World Bank, Washington, DC, 2019)
This study focuses on Sustainable Organic Integrated Livelihoods (SOIL), a U.S.-based nongovernmental organization (NGO), and its operations mostly in Cap-Haitien, Haiti, and to a lesser extent in Port-au-Prince. SOIL, through its container-based program known as EkoLakay, operates mainly in the eastern part of Cap-Haitien in low-income areas characterized by a high population density, irregular alley layout, and higher exposure to floods (compared to the rest of the city). SOIL provides full-cycle ecological sanitation, where excreta is treated and transformed into compost, benefiting agricultural projects and development. SOIL is the only service provider in Cap-Haitien (and in Haiti at large) able to manage a sanitation system that covers the whole sanitation service chain, and customers expressed satisfaction with the toilet technology. While affordability is a key issue for customers and non-customers, the user fee is unlikely to cover all costs of the sanitation service, which includes excreta treatment and transformation. SOIL intends to transfer implementation and scale-up of its CBS business models to the public and private sectors in Haiti, making replicability and scalability key for their business model. To meet its ambitious target number of customers in Cap-Haitien and Port-au-Prince, SOIL will need to continue to influence the institutional environment, along with other organizations and donors in the sector.